(untitled) (Jurnal Bisnis dan Manajemen West Science, 2026)
The internship program is one of the study completions tracks at Nusa Putra University, designed to equip students with real work experience in their respective fields. This report is based on the pre-internship activities at PT. Inovasi Utama Nusantara – MuseAkademi, a company engaged in education and digital training. During the internship, the author was involved in various activities, including creating and editing digital content (social media posts and promotional materials), supporting event promotions and online campaigns, helping to maintain smooth internal and external communication, and contributing ideas to improve branding and audience engagement. The methods used in data collection included observation, interviews, and documentation. The results of these activities are expected to enhance students’ competencies in digital communication, social media management, and teamwork skills, while also providing meaningful contributions to the company in developing its digital-based programs and activities.